The Attentional Repulsion Effect and Relative Size Judgments - Fortenbaugh, Francesca C. (Atten Percept Psychophys, 2019)
Rapid shifts of involuntary attention have been shown to induce mislocalizations of nearby objects. One pattern of mislocalization, termed the Attentional Repulsion Effect (ARE), occurs when the onset of peripheral pre-cues lead to perceived shifts of subsequently presented stimuli away from the cued location. While the standard ARE configuration utilizes vernier lines, to date, all previous ARE studies have only assessed distortions along one direction and tested one spatial dimension (i.e., position or shape). The present study assessed the magnitude of the ARE using a novel stimulus configuration. Across three experiments participants judged which of two rectangles on the left or right side of the display appeared wider or taller. Pre-cues were used in Experiments 1 and 2. Results show equivalent perceived expansions in the width and height of the pre-cued rectangle in addition to baseline asymmetries in left/right relative size under no-cue conditions. Altering cue locations led to shifts in the perceived location of the same rectangles, demonstrating distortions in perceived shape and location using the same stimuli and cues. Experiment 3 demonstrates that rectangles are perceived as larger in the periphery compared to fixation, suggesting that eye movements cannot account for results from Experiments 1 and 2. The results support the hypothesis that the ARE reflects a localized, symmetrical warping of visual space that impacts multiple aspects of spatial and object perception.